DEVELOPMENT OF PANDEMIC IMPACT SCENARIO OF COVID-19 IN THE NATIONAL OIL AND GAS SECTOR YEAR 2020-2021 - Hari Purwanto (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this studies is to analyze the resilience of oil and gas industry facing the multi crises faced during the pandemic and post pandemic of Covid-19. The studies uses the concepts of disasters resilience, economic resilience and resilience on oil and gas energy. The method used is PESKH2 as the external risk factor coupled with timeline of events related to oil and gas during the pandemic as the internal risk of national oil and gas industry and planning scenario for 2020-2021. The study found 12 external risks issues and 17 internal risk issues in operational sectors and supply chain of national oil and gas industry. Threat coefficient analysis shows that the highest hazard and exposure score is economic issue with the score of 8.7 and health risk issue with the score 8.5. These scores show uncertainty of Covid-19 pandemic impact for oil and gas industry in 2020-2021. It is recommended for policy maker to lowering the gas retail price, to assess the potential losses national oil and gas industry, to assess the fiscal capacity for subsidizing he imported oil and gas and to maximize the capacities of domestic oil refineries and the availability of gases sources during and after pandemic to overcome the dependencies from imported oil and gases that burdening the state budgets in the future.